Biodiversity Conservation Strategy and Creative Economic Ecotourism in Tesbatan, Amarasi District, Kupang Regency - Marpaung, Sutan Sahala Muda; Oktaviani, Eva; Rusadi, Nusrah; Kurniawan, Hendra; Syah, Firman; Rina, Timotius Ragga; Asalang, Protus Hyasintus; Pratiwi, Gadis Kartika (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The Tesbatan region, located in the Amarasi District of Kupang Regency, is rich in biodiversity and local cultural heritage, making it a potential hub for ecotourism development. This study aims to develop a comprehensive strategy for biodiversity conservation and creative economic ecotourism to promote sustainable growth in the region. The primary objective is to combine conservation efforts with local economic empowerment through creative industries such as handicrafts, traditional cuisine, and cultural performances. This research utilizes a systematic approach that includes field surveys, literature reviews, and the application of tools like MICMAC, MACTOR, and ISM for data analysis. Data was collected through observations, interviews, questionnaires, and Focus Group Discussions (FGDs) with local stakeholders. The study identifies key variables, influences, and stakeholders involved in the management of biodiversity and ecotourism. The findings suggest that integrating biodiversity conservation with ecotourism and creative economic activities can enhance both environmental sustainability and local community welfare. The proposed strategies involve strengthening local institutions, promoting participatory resource management, and developing integrated ecotourism attractions. In conclusion, this research provides a practical framework for managing Tesbatan’s natural and cultural assets sustainably, fostering both environmental protection and socio-economic development.